Kpocc-peфepeнцuя kak чacmъ omнoшeнuŭ мeжcoy oбъekmaмu u uz нauмeнoвaнuямu b мeouцuнckoм mekcme - Zagórska, Bożenia; Zaniewski, Jan (Glottodidactica, 2005)
Teaching of the Russian language to students reveals certain difficulty concerning the semantic contents of the scientific text on the lexical level. Cross-reference, whose purpose is to convey the meaning and connection of sentences, is one of the types of semantic coherence and clarity of the text. The traditionally understood anaphoric word does not ensure a wide range of modes of nomination in the text. Nomination of objects in the text illustrates the relations between objects and their names that warrant establishing of the following cross-references: 1) one object - one name, 2) different objects - different names, 3) one object - different names, 4) different objects - one name. The analysis was conducted based on Russian and French medical texts.